The art of building in the classical world - Senseney, John R. (Cambridge, UK ; New York)
xv, 245 sayfa
Keywords: “This book examines the application of drawing in the design process of classical architecture, exploring how the tools and techniques of drawing developed for architecture subsequently shaped theories of vision and representations of the universe in science and philosophy. Building on recent scholarship that examines and reconstructs the design process of classical architecture, John R. Senseney focuses on technical drawing in the building trade as a model for the expression of visual order, showing that the techniques of ancient Greek drawing actively determined concepts about the world. He argues that the uniquely Greek innovations of graphic construction determined principles that shaped the massing, special qualities, and refinements of buildings and the manner in which order itself was envisioned.” --